Creation of Professionalism in Public Services by Developing the Competence of State Civil Apparatuses - Endang Try Setyasih (GoAcademica Research & Publishing, 2019)
The era of globalization demands a change in the paradigm of public service in government characterized by clean government or what is known as good governance. This has become a concern for the local government. The effect is that the state civil apparatus, or ASN, is required to provide quality public services based on the principle of public service. For this reason, a strategy is needed to build ASN competencies that include knowledge, skills, and attitudes. Therefore, the research aims to analyze the competency development of the State Civil Apparatus in creating public service professionalism. This research uses a qualitative approach with descriptive methods. The results of the study show that the creation of public service professionalism is highly dependent on the development of ASN competencies related to public services. This is supported by performance, employee accountability, employee loyalty, and employee capabilities. In this study, the authors suggest 6 points that can create public service professionalism if ASN competence is increased, namely increasing accountability, strengthening a sense of nationalism, forming public ethics, fostering an anti-corruption attitude, creating quality commitment, and providing optimal public services.